Thermal responsive photopolymerization 3D printed shape memory polymers enhanced by heat transfer media. Issue 8 (13th December 2022) - Yang, Shuochen; Chen, Tingjun; Bu, Zesen; Tuo, Xiaohang; Gong, Yumei; Guo, Jing
Abstract: Photosensitive resins are the research and development foundation of photopolymerization 3D printed products. We have found that cyclic trimethylolpropane formal acrylate (CTFA) and 2‐phenoxy ethyl acrylate (PHEA) resins are suitable for UV‐curable 3D printing consumables. Their photopolymers exhibit excellent shape memory characteristics at shape change temperature, shape recovery speed, shape extension limit, and shape maintenance ability. Moreover, we have analyzed the internal and external factors affecting these shape memory characteristics through several tests, including multi‐scale structure observation, thermal analysis, and mechanical tests. Furthermore, the complex hollow model design and multiple heat transfer media are adopted to expand the concept of additive manufacturing, and improve the practicability of 4D printing intelligent products. Abstract : The photopolymerization resins used in this paper have been ignored by researchers, but they have unique properties. The engineering design of 3D model is convenient for exerting heat transfer medium, such as liquid metal. The operating temperature of photopolymer composites is between 50 and 70 °C, which is suitable for human life scenarios. The various properties of 3D printed products change by adjusting the monomer proportion and processing parameters. The materials studied in this paper have excellent shape recovery performance, and 3D printed products can grasp a 500g metal ball.